Astronomy in Science and in Human Culture: Jawaharlal Nehru Memorial Lecture 1969 - CHANDRASEKHAR, PROFESSOR S. (SCHOOL SCIENCE, 2006)
It is hardly necessary for me to say how deeply sensitive I am to the honour of giving this second lecture in this series founded in the memory of the most illustrious name of independent modern India. As Pandit Jawaharlal Nehru has written, “The roots of an Indian grow deep into the ancient soil; and though the future beckons, the past holds back.”